Makna Kematian pada Wanita Lanjut Usia yang Melajang - Fahmi Mahmudayati Pratiwi; Irfan Fahmi; Anwar Supenawinata (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
The purpose of this study is to explore how the meaning of death for subjects who are single elderly women. For humans, death has a double meaning that can be interpreted as a positive thing if humans do good things during their lifetime and can also be interpreted as a negative thing if humans commit bad deeds during their lifetime. This study used a qualitative approach with phenomenology methods. The participant of this study was a single elderly woman. The results in this study indicate that the subject means death as a positive thing, namely by getting closer to the Creator.